The genomic and seroprevalence of human bocavirus in healthy Chinese plasma donors and plasma derivatives. Issue 1 (22nd July 2014) - Li, Hongxue; He, Miao; Zeng, Peibin; Gao, Zhan; Bian, Guohui; Yang, Chunhui; Li, Wuping
<x xml:space="preserve">Abstract</x> Background Human bocavirus (HBoV) is a novel parvovirus identified in 2005. It has mostly been detected in respiratory and enteric infections and has not been studied large scale in blood products in relation to transfusion. Study Design and Methods An in‐house quantitative polymerase chain reaction (Q‐PCR) was developed to test HBoV DNA in plasma and plasma derivatives. Plasma samples (n = 6096) collected from healthy donors, 241 plasma pools, and 326 plasma derivatives were screened for HBoV DNA by Q‐PCR. Positive samples were confirmed by nested PCR and further amplified for sequence analysis and phylogenetic studies. The prevalence of immunoglobulin (Ig)G and IgM specific to HBoV structural proteins was measured by enzyme‐linked immunosorbent assay in 209 samples grouped according to virus load (Group 1, HBoV DNA >104 copies/mL; Group 2, HBoV DNA >5 × 102 copies/mL but below 104 copies/mL; Group 3, HBoV DNA negative). Results The genomic prevalence of HBoV in the plasma donors was 9.06%, ranging from 5.01 × 102 to 3.02 × 106 copies/mL. HBoV‐specific IgG and IgM were detected at 20.00 and 7.50% in Group 1, at 20.29 and 2.90% in Group 2, and at 13.00 and 4.0% in Group 3, respectively. Phylogenetic analyses proved that HBoV Genotype 1 was the prevalent genotype in Chinese plasma donors. Conclusion Low levels of HBoV DNA were detectable at high prevalence in Chinese plasma donors and plasma derivatives. Further study is needed to determine whether HBoV screening is necessary.